Information and Communication Technology in Industry 4.0 - Abd Rahman Abdul Rahim; Robiah Ahmad (Proceeding International Conference on Information Technology and Business, 2018)
This paper presents an overview of information and communication technology (ICT) in the era of Industry 4.0. Due to rapid advancement in ICT and the more powerful computing power of computer hardware and increase speed of the internet, the development and integration of IT, internet and other devices has grown exponentially. E-commerce, internet of things, big data, deep learning, augmented reality and smart city are just few of the areas with increased application which is forecasted to have exponential growth in few years to come.Keywords:E-commerce; Internet of things (IoT); big data; deep learning; virtual augmented reality, smart city